Scoping review of enablers and challenges of implementing pharmacogenomics testing in the primary care settings - Chun-Wai Mai; Sathvik B Sridhar; Mohammed Salim Karattuthodi; Perishithaa M Ganesan; Javedh Shareef; E Lyn Lee; Keivan Armani (BMJ Open)
Introduction Pharmacogenomic testing (PGx) plays a crucial role in improving patient medication safety, yet ethical concerns and limitations impede its clinical implementation in the primary care settings.Aims To systematically review the current state of PGx in the primary care settings and determine the enablers and challenges of its implementation.Design A scoping review was carried out by adhering to Arksey and O’Malley’s 6-stage methodological framework and the 2020 Joanna Briggs Institute and Levac et al.Data sources Cochrane Library, EMBASE, Global Health, MEDLINE and PubMed were searched up to 17 July 2023.Eligibility criteria All peer-reviewed studies in English, reporting the enablers and the challenges of implementing PGx in the primary care settings were included.Date extraction and synthesis Two independent reviewers extracted the data. Information was synthesised based on the reported enablers and the challenges of implementing PGx testing in the primary care settings. Information was then presented to stakeholders for their inputs.Results 78 studies discussing the implementation of PGx testing are included, of which 57% were published between 2019 and 2023. 68% of the studies discussed PGx testing in the primary care setting as a disease-specific themes. Healthcare professionals were the major stakeholders, with primary care physicians (55%) being the most represented. Enablers encompassed various advantages such as diagnostic and therapeutic benefits, cost reduction and the empowerment of healthcare professionals. Challenges included the absence of sufficient scientific evidence, insufficient training for healthcare professionals, ethical and legal aspects of PGx data, low patient awareness and acceptance and the high costs linked to PGx testing.Conclusion PGx testing integration in primary care requires increased consumer awareness, comprehensive healthcare provider training on legal and ethical aspects and global feasibility studies to better understand its implementation challenges. Managing high costs entails streamlining processes, advocating for reimbursement policies and investing in research on innovation and affordability research to improve life expectancy.